Arabic Language Learning in the Post-Method Era: Evaluating ICT-Driven Environmental Engineering for Enhanced Communicative Skills - Muhbib Abdul Wahab; Ubaid Ridlo; Raswan Raswan; Shifany Maulida Hijjah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Arabic language learning in non-native settings often encounters a disconnection between linguistic proficiency and socio-cultural contexts, leading to mother-tongue interference in communication. This study aims to analyze the integration of cultural competence (al-kifâyah al-tsaqâfiyyah) into Arabic pedagogy to bridge this gap across six State Islamic Higher Education Institutions (PTAIN) in Java. Utilizing a multi-site comparative qualitative approach and SWOT analysis, the research evaluates environment-based language and culture learning models. Findings indicate that language acquisition effectiveness depends significantly on environmental engineering that synergizes formal and informal aspects while internalizing native patterns of thinking (anmâth al-tafkîr) and expression (anmâth al-ta’bir). Integrating Arabic-Islamic cultural content into the curriculum and syllabus through an integrated system is proven to enhance communicative skills and eliminate psychological barriers for students. This study recommends reformulating learning designs that position culture as a vital instrument in achieving authentic and functional language proficiency.